Reproductive health services for refugees by refugees in Guinea I: family planning - Newey Claire; Blankhart David; von Roenne Anna; Souare Yaya; Kollie Sarah; Howard Natasha; Chen Mark I; Borchert Matthias (Conflict and Health, 2008)
Abstract Background Comprehensive studies of family planning (FP) in refugee camps are relatively uncommon. This paper examines gender and age differences in family planning knowledge, attitudes, and practices among Sierra Leonean and Liberian refugees living in Guinea. Methods In 1999, a cross-sectional survey was conducted of 889 reproductive-age men and women refugees from 48 camps served by the refugee-organised Reproductive Health Group (RHG). Sampling was multi-stage with data collected for socio-demographics, family planning, sexual health, and antenatal care. Statistics were calculated for selected indicators. Results Women knew more about FP, although men's education reduced this difference. RHG facilitators were the primary source of reproductive health information for all respondents. However, more men then women obtained information from non-health sources, such as friends and media. Approval of FP was high, significantly higher in women than in men (90% vs. 70%). However, more than 40% reported not having discussed FP with their partner. Perceived service quality was an important determinant in choosing where to get contraceptives. Contraceptive use in the camps served by RHG was much higher than typical for either refugees' country of origin or the host country (17% vs. 3.9 and 4.1% respectively), but the risk of unwanted pregnancy remained considerable (69%). Conclusion This refugee self-help model appeared largely effective and could be considered for reproductive health needs in similar settings. Having any formal education appeared a major determinant of FP knowledge for men, while this was less noticeable for women. Thus, FP communication strategies for refugees should consider gender-specific messages and channels.